Expression and Functional Analysis of the Propamocarb-Related Gene CsMCF in Cucumber - Zhang, Fan; Xin, Ming; Yu, Siqi; Liu, Dong; Zhou, Xiuyan; Qin, Zhiwei (Frontiers in Plant Science, 2019)
Propamocarb (PM), a carbamate fungicide, can effectively control downy mildew on cucumber. However, due to the large-scale and high-dose use of this fungicide, PM residues have become a major problem in cucumber production. In this report, the cucumber cultivar 'D0351' (with the lowest residual PM content) and the cucumber cultivar 'D9320' (with the highest residual PM content) were used as experimental materials. The candidate gene CsMCF, which is related to a low residual PM content in cucumber, was screened by high-throughput tag-sequencing (Tag-Seq) and PM analysis, and its role in reducing PM residue in cucumber was explored. CsMCF was cloned and obtained. This gene contains an open reading frame of 1026 bp, encodes 341 amino acids and contains 3 Mito_carr domains. The encoded protein is a hydrophobic protein with 4 distinct transmembrane structures but no signal peptide cleavage sites. The subcellular localization of the protein is the cytoplasm. Evolutionary tree analysis showed that CsMCF had the highest homology to a gene from the melon Cucumis melo L. (XM_008464998.2). The core elements of the promoter include cis-acting elements, such as those related to salicylic acid (SA), jasmonic acid (JA), gibberellin (GA), and abscisic acid (ABA). Following PM treatment, CsMCF was significantly upregulated at most time points in different parts of the fruit, leaf, stem and root of 'D0351', while expression was downregulated at most time points in the fruit, leaf and stem of 'D9320'. The order of the expression levels in different cucumber organs was as follows: fruit>leaf>stem>root. CsMCF was specifically expressed in the stems and leaves of 'D0351'. The PM residues in CsMCF (+)-overexpressing T0 and T1 cucumber fruits were significantly lower than those in the wild type, while the PM residues in CsMCF (-)-overexpressing T0 and T1 cucumber fruits were significantly higher. The qRT-PCR results showed that CsMCF can respond to biotic and abiotic stresses, actively respond to PM treatment and play a role in reducing PM residues in cucumber fruits.